2014
DOI: 10.1039/c3cp52845f
|View full text |Cite
|
Sign up to set email alerts
|

Probing the specific ion effects of biocompatible hydrated choline ionic liquids on lactate oxidase biofunctionality in sensor applications

Abstract: This paper presents an extended study on the ion effects of a series of biocompatible hydrated choline based ionic liquids (ILs) on lactate oxidase (LOx), an important enzyme in biosensing technology for the in vitro detection of lactic acid. Secondary structural analysis revealed changes in the protein conformation in hydrated ILs, while thermal unfolding/aggregation dynamics showed different profiles in the presence or absence of ILs. Moreover, LOx thermally denaturised at 90 1C showed residual activity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…The Yang group found that the activity of mushroom tyrosinase in 5.85% (w/v) ILs follows a reverse Hofmeister series: [Cholinium][OAc] < [Cholinium][MeSO 3 ] < [Cholinium][NO 3 ] and [Bu 4 N][OAc] < [Bu 4 N][MeSO 3 ]; the likely explanation is that kosmotropic anions interact with Cu 2+ of the metalloenzyme, resulting in lower activities. Curto et al observed the activity of lactate oxidase in 0.5 mol L −1 choline‐based ILs follows a decreasing order with anions as Cl − > H 2 PO 4 − > NO 3 − > Levulinate − > HCOO − . The viscosity B ‐coefficients for these anions at 25°C (in dm 3 mol −1 ) are: Cl − (−0.005), H 2 PO 4 − (0.340), NO 3 − (−0.043) and HCOO − (0.052) .…”
Section: Specific Ion Effect Of Ils On Protein Structures and Enzyme mentioning
confidence: 99%
“…The Yang group found that the activity of mushroom tyrosinase in 5.85% (w/v) ILs follows a reverse Hofmeister series: [Cholinium][OAc] < [Cholinium][MeSO 3 ] < [Cholinium][NO 3 ] and [Bu 4 N][OAc] < [Bu 4 N][MeSO 3 ]; the likely explanation is that kosmotropic anions interact with Cu 2+ of the metalloenzyme, resulting in lower activities. Curto et al observed the activity of lactate oxidase in 0.5 mol L −1 choline‐based ILs follows a decreasing order with anions as Cl − > H 2 PO 4 − > NO 3 − > Levulinate − > HCOO − . The viscosity B ‐coefficients for these anions at 25°C (in dm 3 mol −1 ) are: Cl − (−0.005), H 2 PO 4 − (0.340), NO 3 − (−0.043) and HCOO − (0.052) .…”
Section: Specific Ion Effect Of Ils On Protein Structures and Enzyme mentioning
confidence: 99%
“…22,23 Amongst a variety of ILs, choline-based ILs are considered to be promising, low toxicity ILs for a variety of biomedical applications. [24][25][26] This is mostly due to the fact that choline (more correctly cholinium) is a naturally occurring cation that shows very low toxicity and it can work as a cell signaling agent. 27,28 Choline salts have also been used recently in IL-gel systems for cancer therapy delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Kaar and coworkers have recently demonstrated the use of 2D NMR methods as a means to understand and improve enzyme stability in ILs (Nordwald, Armstrong, & Kaar, 2014). Common activity assays have also been used including calorimetry (Curto et al, 2014), activity and conformational stability assays (Nordwald & Kaar, 2013a, 2013b, and fluorescence quenching assays to find the extent of ion binding to the enzyme surface (Nordwald & Kaar, 2013a). Kinetic studies using ultraviolet-visible spectroscopy or other techniques have yielded Michaelis-Menten constants (Ajloo et al, 2013;Curto et al, 2014;Ghaedizadeh et al, 2016), and quantitative structureactivity relationship models have been developed to predict enzyme performance in ILs (Mai & Koo, 2014).…”
Section: Experiments Of Biocatalysis In Ilsmentioning
confidence: 97%
“…Difficulties arising from the use of nonaqueous solvents have prevented the use of many of the typical analysis techniques used to study enzymes. Many papers that have been published thus far that deal specifically with enzymes in ILs utilize techniques such as circular dichroism (CD) (Curto et al, 2014;Ghaedizadeh et al, 2016), differential scanning calorimetry (Dabirmanesh et al, 2011), and fluorescence spectroscopy techniques (Ajloo, Sangian, Ghadamgahi, Evini, & Saboury, 2013;Dabirmanesh et al, 2011;Ghaedizadeh et al, 2016;Ghosh, Parui, Jana, & Bhattacharyya, 2015) to observe dynamics and conformational changes upon insertion in the IL. Dynamic light scattering has been used to observe enzyme aggregation or large-scale denaturation in ILs (Jaeger & Pfaendtner, 2013).…”
Section: Experiments Of Biocatalysis In Ilsmentioning
confidence: 98%
See 1 more Smart Citation